Where's the Crime? Exploring Divergences Between Call Data and Perceptions of Local Crime. (11th October 2019) - Porter, Lauren C; Curtis, Andrew; Jefferis, Eric; Mitchell, Susanne
Abstract: Scholars typically use calls to the police to study crime patterning; however, crime reporting may be systematic across space. Using spatial video and geonarrative methodology, we investigate the overlap between perceived crime hot spots among 35 neighbourhood insiders (police officers, ex-offenders and residents) and hot spots gleaned from call data. In general, perceptual hot spots diverge from call data, but in particular, a corner store emerges as a perceptual hot spot across all groups, but not in call data. We use our data to explore the microgeographic dynamics of this 'hidden hot spot'. We find that the corner store is relatively isolated, with few occupied residences around it and participants avoiding it. In addition, our geonarratives suggest that the store lacks adequate guardianship. We argue that mixed methodological approaches such as these are useful for understanding discrepancies between measures as well as the situational and environmental dynamics of problem places.